Biological Activities of Z-Lycopenes Contained in Food - Sato, Kana; Shindo, Kazutoshi; Sakemi, Yuka; Honda, Masaki; Hara, Kurumi (Journal of Oleo Science, 2020)
Mono-(5Z)-, -(9Z)-, and -(13Z)-lycopenes are found in food containing processed tomato products, while tetra-Z-(7Z, 9Z, 7′Z, 9′Z)-lycopene (prolycopene) is found in tangerine-strain tomatoes. We prepared pure mono-Z-lycopenes from all-E-lycopene via chemical reaction (heating in CH2Cl2 at 80℃ for 1 h) followed by purification using preparative silica gel HPLC, while prolycopene was isolated from tangerine tomatoes by partitioning with n-hexane and 90% MeOH followed by silica gel column chromatography. A simple method of distinguishing the mono-Z-lycopenes using the 13C NMR chemical shifts of their Z-methyl carbons is proposed. Additionally, the 1O2 quenching and 3T3-L1 cell differentiation activities of the compounds were then compared with all-E-lycopene for the first time. All the evaluated Z-isomers showed 1O2 quenching activities that were equal to or slightly lower than that of all-E-lycopene, with the IC50 values for the 1O2 quenching activities of (all-E)-, (5Z)-, (9Z)-, (13Z)-, and (7Z, 9Z, 7′Z, 9′Z)-lycopene being 4.4±0.36, 4.0±1.44, 5.3±1.08, 6.9±1.67, and 8.7±0.34 µM, respectively. The mouse 3T3-L1 cell differentiation activities followed the order: (all-E) > (9Z) > (5Z) ≈ (9Z) ≈ (13Z) ≈ (7Z, 9Z, 7′Z, 9′Z).